Econometrics Applications On Developing Economies Data ; Some Restrications - الفاخري, محمود (Dirasat in Economics and Business, 2006)
One of the main problems which usually faced by researchers when trying to use applied econometrics in developing economies is that of data complation ,for example ; the use of regretssion equations for drawing policy implication and hypothesis testing depends on the significant of their individual coefficient , which depends on data availability and reliability In this paper we discussed some ralated proplems (such as, multicollinearity, autocorrelation, specification errors , idetification proplem , cointegration .....) and their implications when dea-ling with developing economies. However most developing economies are more or less alike in their poor means of data collection more over it is usually available on annual basis and for a limmited time period.